Ontological Analyses in Science, Technology and Informatics - Maseleno, Andino; Othman, Marini (IntechOpen, 2020)
Advance exact science of nowadays inherited the original ontology's its efforts to systemize and conceptualize. In this respect the concept of ontology is now a non-speculative methodology for both studying reality objects and its used tools, which both instruments are important for our orientation in the space of physical, technical, mental and societal world. So, within the exactly considered ontology, we deal with the process of studying, as well as with the outcome of such studying of the objects observed or created by man and their respective made by man concepts, relations between them and relations between their systems in the fields of the given scientific branches. This book Ontological Analyses in Science, Technology and Informatics - the second volume released within the framework of the IntechOpen project in this field - is the illustration of application of the concept of ontology approach understood in the modern and exact way, it is the presentation of the Ontology science. This book covers the examples of the modern ontology approach, especially the approach in the branch of the Information Science dealing with the Inference and Proof, Knowledge patterns, Cross-Application Communication, Diagnosis and Expert systems in Health and Food and the Taxonomy problems.The intended readers of this book are researchers, students and all the practitioners in the field.